Propionic Acid and Fasudil as Treatment against Rotenone Toxicity in an In Vitro Model of Parkinson’s Disease - Ostendorf, Friederike (Molecules, 2020)
Parkinson’s disease (PD) is a multifactorial neurodegenerative disease. In recent years, several studies demonstrated that the gastroenteric system and intestinal microbiome influence central nervous system function. The pathological mechanisms triggered thereby change neuronal function in neurodegenerative diseases including dopaminergic neurons in Parkinson´s disease. In this study, we employed a model system for PD of cultured primary mesencephalic cells and used the pesticide rotenone to model dopaminergic cell damage. We examined neuroprotective effects of the Rho kinase inhibitor Fasudil and the short chain fatty acid (SCFA) propionic acid on primary neurons in cell morphological assays, cell survival, gene and protein expression. Fasudil application resulted in significantly enhanced neuritic outgrowth and increased cell survival of dopaminergic cells. The application of propionic acid primarily promoted cell survival of dopaminergic cells against rotenone toxicity and increased neurite outgrowth to a moderate extent. Interestingly, Fasudil augmented gene expression of synaptophysin whereas gene expression levels of tyrosine hydroxylase (TH) were substantially increased by propionic acid. Concerning protein expression propionic acid treatment increased STAT3 levels but did not lead to an increased phosphorylation indicative of pathway activation. Our findings indicate that both Fasudil and propionic acid treatment show beneficial potential in rotenone-lesioned primary mesencephalic cells.